Nutrient and Silicon Isotope Dynamics in the Laptev Sea and Implications for Nutrient Availability in the Transpolar Drift - Laukert, G.; Grasse, P.; Novikhin, A.; Povazhnyi, V.; Doering, K.; Hölemann, J.; Janout, M.; Bauch, D.; Kassens, H.; Frank, M.; Grasse, P.; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Germany; Novikhin, A.; 5 AARI Arctic and Antarctic Research Institute Saint Petersburg Russia; et al. (Global Biogeochemical Cycles, 2022)
Realistic prediction of the near‐future response of Arctic Ocean primary productivity to ongoing warming and sea ice loss requires a mechanistic understanding of the processes controlling nutrient bioavailability. To evaluate continental nutrient inputs, biological utilization, and the influence of mixing and winter processes in the Laptev Sea, the major source region of the Transpolar Drift (TPD), we compare observed with preformed concentrations of dissolved inorganic nitrogen (DIN) and phosphorus (DIP), silicic acid (DSi), and silicon isotope compositions of DSi (δ30SiDSi) obtained for two summers (2013 and 2014) and one winter (2012). In summer, preformed nutrient concentrations persisted in the surface layer of the southeastern Laptev Sea, while diatom‐dominated utilization caused intense northward drawdown and a pronounced shift in δ30SiDSi from +0.91 to +3.82‰. The modeled Si isotope fractionation suggests that DSi in the northern Laptev Sea originated from the Lena River and was supplied during the spring freshet, while riverine DSi in the southeastern Laptev Sea was continuously supplied during the summer. Primary productivity fueled by river‐borne nutrients was enhanced by admixture of DIN‐ and DIP‐rich Atlantic‐sourced waters to the surface, either by convective mixing during the previous winter or by occasional storm‐induced stratification breakdowns in late summer. Substantial enrichments of DSi (+240%) and DIP (+90%) beneath the Lena River plume were caused by sea ice‐driven redistribution and remineralization. Predicted weaker stratification on the outer Laptev Shelf will enhance DSi utilization and removal through greater vertical DIN supply, which will limit DSi export and reduce diatom‐dominated primary productivity in the TPD. Plain Language Summary: Ongoing warming and sea ice loss in the Arctic Ocean may significantly impact biological productivity, which is mainly controlled by light and nutrient availability. To investigate nutrient inputs from land, biological utilization, and the ...